A taxonomy of skills for futuristic hadith studies with special reference to skills of translation - Mohd Marzuki, Zunaidah (2021)
This study proposes a taxonomy of skills for futuristic Hadith Studies by highlighting the necessity of translation skills needed in translating Hadith and its related sciences as well as its problem and possible solution.